2007
DOI: 10.1196/annals.1384.006
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin

Abstract: Oxytocin (OT) is a neuropeptide that is produced primarily in the hypothalamus and is best known for its role in mammalian birth and lactation. Recent evidence also implicates OT in social behaviors, including parental behavior, the formation of social bonds, and the management of stressful experiences. OT is reactive to stressors, and plays a role in the regulation of both the central and autonomic nervous system, including effects on immune and cardiovascular function. Knowledge of patterns of OT release wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
277
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(295 citation statements)
references
References 25 publications
(52 reference statements)
12
277
0
Order By: Relevance
“…As oxytocin (OT) is involved with attachment processes and social behaviour, it was hypothesised that OT release is higher during REM than during NREM sleep. Contrary to this hypothesis, however, is the argument that, as the posterior pituitary is presumed to be the primary source of salivary OT (Carter et al 2007), and as REM sleep in humans begins during decreased secretory activity of the anterior pituitary (Follenius et al 1988), it might be expected that OT release is lower during REM than during NREM sleep (although there are differences in secretory processes between anterior and posterior hypothalamus).…”
Section: Introductionmentioning
confidence: 79%
“…As oxytocin (OT) is involved with attachment processes and social behaviour, it was hypothesised that OT release is higher during REM than during NREM sleep. Contrary to this hypothesis, however, is the argument that, as the posterior pituitary is presumed to be the primary source of salivary OT (Carter et al 2007), and as REM sleep in humans begins during decreased secretory activity of the anterior pituitary (Follenius et al 1988), it might be expected that OT release is lower during REM than during NREM sleep (although there are differences in secretory processes between anterior and posterior hypothalamus).…”
Section: Introductionmentioning
confidence: 79%
“…Besides its effects in social bonding and affiliation in mammals (Lim and Young, 2006), peripheral OT is involved in female reproduction (labor and milk letdown: Blanks and Thornton, 2003;Uvnäs-Moberg et al, 2001) and anxiety reduction (Olff et al, 2013). A broadening body of evidence indicates that these central and peripheral OT pathways can be coordinated (Carson et al, 2014;Carter et al, 2007;O'Byrne et al, 1990;Ross and Young, 2009;Wotjak et al, 1998) and may exert crosslinked effects (Ayers et al, 2011;Madden and Clutton-Brock, 2011;Witt et al, 1990). Other studies indicate independent control mechanisms of central and peripheral OT secretion (Amico et al, 1990;Rosenblum et al, 2002;Seckl and Lightman, 1987).…”
mentioning
confidence: 99%
“…Christensen et al and Ebstein et al [14,15] reported serious problems in the different published OXT levels in studies utilizing the OXT immunoassay kit from ENZO Life Science [16]. OXT levels were very high without use of the extraction protocol as recommended in the manufacturer's instructions for the OXT immunoassay kit (ENZO Life Science) [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we suggest that the development of a high sensitivity and specificity assay that does not require an extraction protocol for OXT will be very important in OXT research as a biomarker of psychiatric disorders for ASD etc. [16]. Furthermore, many studies of OXT as a biomarker have reported to social recognition and memory [17], romantic love, trust, and fear in humans [18], and mind-reading in humans [19].…”
Section: Discussionmentioning
confidence: 99%